Recent updates on correlation between reactive oxygen species and synbiotics for effective management of ulcerative colitis - Ashique, Sumel; Mishra, Neeraj; Garg, Ashish; Sibuh, Belay Zeleke; Taneja, Pankaj; Rai, Gopal; Djearamane, Sinouvassane; Wong, Ling Shing; Al-Dayan, Noura; Roychoudhury, Shatabhisha; Kesari, Kavindra Kumar; Slama, Petr; et al. (Frontiers in Nutrition, 2023)
Ulcerative colitis (UC) is presently considered a multifactorial pathology, which may lead to persistent inflammatory action of the gastrointestinal tract (GIT) because of an improperly managed immunological reactivity to the intestinal microbiota found in the GIT. The immune response to common commensal microbes plays an essential role in intestinal inflammation related to UC synbiotics, and it is an important element in the optimal therapy of UC. Therefore, synbiotics, i.e., a mixture of prebiotics and probiotics, may help control the diseased state. Synbiotics alleviate the inflammation of the colon by lowering the reactive oxygen species (ROS) and improving the level of antioxidant enzymes such as catalase (CAT), glutathione peroxidase (GPX), and superoxide dismutase (SOD). Prebiotic supplementation is not a common practice at the moment, despite numerous research findings proving that the benefits of both probiotics and prebiotics encourage their continued existence and positioning in the GIT, with positive effects on human health by managing the inflammatory response. However, the fact that there have been fewer studies on the treatment of UC with different probiotics coupled with selected prebiotics, i.e., synbiotics, and the outcomes of these studies have been very favorable. The review explores the possible role of reactive oxygen species, SOD, and Synbiotics in managing UC. The proposed article also focuses on the role of alteration of gut microbiota, antioxidant defense in the gastrointestinal tract, and the management of UC. The current review emphasizes oxidative stress signaling in the GI tract, oxidative stress-based pathomechanisms in UC patients, and UC therapies inhibiting oxidative stress's effects.